FRI0535 NEWLY DETECTED HYPERTHYROIDISM WITH THERAPEUTIC INDICATIONS IN RHEUMATIC DISEASE PATIENTS AND HEALTHY CONTROLS IN JAPAN: A RETROSPECTIVE COHORT STUDY. (2nd June 2020) - Fukui, S.; Ikeda, Y.; Kidoguchi, G.; Nakai, T.; Ozawa, H.; Kawaai, S.; Koido, A.; Ohara, Y.; Shimizu, H.; Tamaki, H.; Yamaguchi, K.; Okada, M.
Abstract : Background: Thyroid disorders are known as common comorbidities of rheumatic diseases(RD) [1]. However, data regarding prevalence of hyperthyroidism with treatment indication in RD patients are limited. Objectives: This study aims to reveal and compare the frequency of newly developed hyperthyroidism with treatment indication between RD patients and healthy controls (HC), and identify risk factors to identify patients whose thyroid function should be followed up carefully. Methods: We retrospectively reviewed charts of RD patients and HC who had thyroid stimulating hormone (TSH) measured at least once between 2004 and 2018 from immuno-rheumatology center and preventive medicine center in St. Luke's International Hospital, Japan. We compared frequency of hyperthyroidism requiring treatment (TSH ≦ 0.1μU/mL or for which physicians started treatment) with Kaplan-Meier curve and log rank test. Cox regression multivariate analysis was performed to reveal risk factors for the new onset of hyperthyroidism with treatment indication in participants without treatment-indicated hyperthyroidism at initial assessments. Results: Overall, 2307 RD patients and 78251 HC were included. Newly detected hyperthyroidism with treatment indication were significantly more frequent in RD patients at initial assessment (1.3% vs 0.5 %, p < 0.001) and in total (2.9% vs 1.7%, p<0.001) (Table 1, Figure 1 ). Cox regression multivariate analysis revealed systemic lupus erythematosis (SLE), polymyositis dermatomyositis (PMDM), mixed connective tissue disease (MCTD) as significant risk factors of new developments of hyperthyroidism during follow up after adjusting confounders. (Table 2 ) Conclusion: Hyperthyroidism with therapeutic indications are considerably more frequent in RD patients (particularly with SLE, PMDM and MCTD) both at initial assessment and during follow up. We recommend routine screening at initial assessment and careful follow up of thyroid function test in those patients. References: [1] Rev Bras Rheumatol 2012;52(3):417-430 Disclosure of Interests: None declared